2022
DOI: 10.1002/ange.202215422
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization of Biaryls through Polarity Mismatched Radical Spirocyclization

Abstract: Dearomatization reactions involving radical cyclizations can facilitate the synthesis of complex polycyclic systems that find applications in medicinal chemistry and natural product synthesis. Here we employ redox-neutral photocatalysis to affect a radical spirocyclization that transforms biaryls into spirocyclic cyclohexadienones under mild reaction conditions. In a departure from previously reported methods, our work demonstrates the polarity mismatched addition of a nucleophilic radical to an electron rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…While many reports, including Okada's original work, have suggested that a proton donor can accelerate the fragmentation rate of RAEs [29,49,53], specific values comparing the fragmentation rate constants or the N-O bond dissociation energies of radical anions and neutral radicals derived from RAEs are not available in the literature. Lumb and co-workers recently published a study on the conversion of biaryl-derived NHPI esters into spirocyclic cyclohexadienones through a photocatalytic radical-mediated dearomatization, with H 2 O serving as the nucleophile [54] (Scheme 9A). Despite the presence of H 2 O in the reaction, the reduction of 38 to its corresponding radical anion 39 could occur without the need for hydrogen-bonding (Scheme 9B NHPI esters can also engage in π-π interactions with electronrich species to generate charge-transfer complexes that can absorb light in the visible region.…”
Section: Photocatalytic Oxidative Quenching Mechanismmentioning
confidence: 99%
“…While many reports, including Okada's original work, have suggested that a proton donor can accelerate the fragmentation rate of RAEs [29,49,53], specific values comparing the fragmentation rate constants or the N-O bond dissociation energies of radical anions and neutral radicals derived from RAEs are not available in the literature. Lumb and co-workers recently published a study on the conversion of biaryl-derived NHPI esters into spirocyclic cyclohexadienones through a photocatalytic radical-mediated dearomatization, with H 2 O serving as the nucleophile [54] (Scheme 9A). Despite the presence of H 2 O in the reaction, the reduction of 38 to its corresponding radical anion 39 could occur without the need for hydrogen-bonding (Scheme 9B NHPI esters can also engage in π-π interactions with electronrich species to generate charge-transfer complexes that can absorb light in the visible region.…”
Section: Photocatalytic Oxidative Quenching Mechanismmentioning
confidence: 99%